2013
DOI: 10.1096/fj.13-233262
|View full text |Cite
|
Sign up to set email alerts
|

Antiobese function of platelet‐activating factor: increased adiposity in platelet‐activating factor receptor‐deficient mice with age

Abstract: Platelet-activating factor receptor (PAFR)-deficient mice developed a more severe obese state characterized by higher body mass (~25%) and epididymal fat mass (~55%) with age than that of wild-type (WT) littermates. PAFR-deficient mice did not show changes in the expression of critical genes involved in anabolic and catabolic metabolism in adipose, liver, and muscle tissues between 6 and 36 wk. However, a 38-81% reduction in β3/β1-adrenergic receptor (AR) and uncoupling protein 1 (UCP1) mRNA and protein levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…The cause of this difference might be the age of the animals. While the current study and Parekh et al 3 used young mice (4-6 weeks), Guo et al 20 used relatively older mice (3 months); older animals 27 and humans 28 exhibit greater difficulty in losing body mass compared to younger individuals even with calorie restriction.…”
Section: Discussionmentioning
confidence: 59%
“…The cause of this difference might be the age of the animals. While the current study and Parekh et al 3 used young mice (4-6 weeks), Guo et al 20 used relatively older mice (3 months); older animals 27 and humans 28 exhibit greater difficulty in losing body mass compared to younger individuals even with calorie restriction.…”
Section: Discussionmentioning
confidence: 59%
“…Our group and others have recently demonstrated that PAF signaling pathways appear to regulate glucose metabolism and fat accumulation in adipocytes by controlling adipose tissue inflammation [11,14]. PAFR -/-mice fed HC diet show an increased fat pad expansion with less adipose tissue inflammation compared with WT-HC mice.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…PAF activates a specific receptor (PAFR) that is expressed on the plasma membrane of various cell types [13]. Although this molecule is a potent phospholipid activator and mediator of many inflammatory responses, recent data have added new roles of PAF in metabolic control and fatty acid synthesis [11,14]. Animals lacking PAFR exhibit a hyporesponsive inflammation in several experimental models [11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In brown adipose tissue, the PAFR activation was shown to up-regulate the expression of beta 3 adrenergic receptor and Uncoupling Protein 1, which are essential for cellular thermogenesis. These results suggest an additional mechanism where PAFR plays a role in metabolism by regulating energy expenditure (18). Addionally, studies in rats using Rupafin (Rupatadine), an antagonist of PAFR and H1 histamine receptors, showed microscopic liver findings in rats which comprised vacuolation of hepatocytes an increased incidence of fatty change (35).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, their results suggest that the anti-obesity effect of PAFR is due to impaired energy expenditure. Regarding WAT inflammation, they found that the CD11c+ macrophage (M1) population was increased in PAFR-deficient mice, although they did not find any increased levels of pro-inflammatory markers (17,18). Contrarily, Menezes-Garcia et al found that PAFR deficiency resulted in decreased inflammation in the adipose tissue and improved glucose metabolism (19).…”
Section: Introductionmentioning
confidence: 99%